To the Problem of Integrative (Complex) Type of Understanding Law - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2022)
This scientific article analyzes the positions of scientists in relation to the integrative (complex) type of legal understanding. Arguments of its opponents and supporters, advantages, as well as certain interpretations of law from the standpoint of this approach are given. The groundlessness of identifying an integrated approach with a broad understanding of law is emphasized.